Penguatan Kapasitas Digital Sekolah Melalui Implementasi ZYA CBT: Studi Kasus di MTs. Miftahul Falah Bandung - Hidayat, Asep; Andriana; Zulkarnain (Jurnal Pengabdian Tri Bhakti, 2025)
The digital transformation of education demands innovative solutions for assessment systems that are still dominated by paper-based tests. MTs. Miftahulfalah Bandung faces challenges such as limited capacity of IT administrators in managing online test applications, teachers’ unfamiliarity with digital question banks, and students’ lack of experience in computer-based examinations. This community service project aimed to strengthen digital capacity through the implementation of the ZYA Computer Based Test (CBT) application. Using the ADDIE instructional design model, the program included needs analysis, training module design, system development, guided workshops, and comprehensive evaluation. Results demonstrated significant improvement in participants’ competencies, with post-test scores rising by 41.67% for IT administrators, 45.45% for teachers, and 56% for students. Participant satisfaction was also high, with an average Likert score of 4.5, indicating strong acceptance of the training. These findings confirm that the ADDIE-based training approach effectively supports the adoption of digital assessment systems in schools. The implications highlight that ZYA CBT can serve as a sustainable solution to enhance digital literacy, efficiency, and readiness for national computer-based assessments.